How to Perform and Interpret Balloon Expulsion Test - Lee, Bong Eun; Kim, Gwang Ha (Journal of neurogastroenterology and motility, 2014)
The balloon expulsion test is a simple and useful method for investigating a defecatory disorder assessing the subject's ability to evacuate a simulated stool. However, there is no standard methodology and varying interpretations have been reported. This review discusses the techniques, interpretation and clinical utility of the balloon expulsion test.